High performance solution-processable tetrathienoacene (TTAR) based small molecules for organic field effect transistors (OFETs). Issue 43 (17th May 2017) - Vegiraju, Sureshraju; Huang, Deng-Yi; Priyanka, Pragya; Li, Yo-Shan; Luo, Xian-Lun; Hong, Shao-Huan; Ni, Jen-Shyang; Tung, Shih-Huang; Wang, Chien-Lung; Lien, Wei-Chieh; Yau, Shueh Lin; Liu, Cheng-Liang; et al.
Abstract : DDTT-TTAR exhibits the highest mobility of 0.81 cm 2 V −1 s −1 . Abstract : Three new organic semiconductors with alkyl chain-substituted tetrathienoacene (TTAR) as the central core and both ends capped with thiophene (DT-TTAR), thienothiophene (DTT-TTAR) and dithienothiophene (DDTT-TTAR) have been synthesized and characterized for organic field effect transistor (OFET) applications. A hole mobility of 0.81 cm 2 V −1 s −1 was achieved for the DDTT-TTAR film, which represents the highest mobility yet found for a solution-processable p-type TTAR-based small molecular semiconductors.